The Management of Power System Reliability in the Offshore Oil and Gas Field - Reinhard, Welly; Yulius, Gustav; Sarasi, Vita; Harsanto, Budi; Azis, Yudi; Yunani, Akhmad (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
The reliability of electric power systems is needed in offshore oil and gas field operations because disruptions can have a direct impact on oil production, costs, and company profits.Objectives: to determine the evaluation of reliability performance and propose a model for managing the power system reliability of the PHE OSES offshore oil and gas field.Methodology: A case study with data collected through observation, interviews, and analysis of relevant documents.Finding: Reliability in 2015-2016 has not reached the target but from 2017-2021 has reached the target of 97.5%, as well as availability in 2015, 2018, 2019 & 2020 has not reached the target but in 2016, 2017 & 2021 has reached the target of 95%. This resulted in the highest production losses in 2015 at 266,965 and the lowest in 2021 at 21,388 barrels of oil. The model is proposed by combining elements in risk-based asset management method, RCM method, and redesign.Conclusion: In recent years, reliability has been on target but availability is volatile. The model is proposed to maintain reliability & availability on target so that production losses can be minimized.